IMMU-16. TARGETING GLYPICAN 2 (GPC2) ON PEDIATRIC MALIGNANT BRAIN TUMORS WITH MRNA CAR T CELLS. (1st June 2021) - Foster, Jessica; Griffin, Crystal; Stern, Allison; Brimley, Cameron; Buongervino, Samantha; Storm, Phillip; Barrett, David; Maris, John; Resnick, Adam; Bosse, Kristopher
Abstract: Glypican 2 (GPC2) is a cell-surface oncoprotein initially identified in neuroblastoma, retinoblastoma, and medulloblastoma as an ideal target for immunotherapy (Cancer Cell, 2017). Here we evaluated GPC2 expression across the spectrum of pediatric brain tumors using RNA sequencing from specimens in the Children's Brain Tumor Network (CBTN). High GPC2 expression, defined as >10 FPKM, was found in 100% of embryonal tumors with multilayered rosettes (ETMRs) (n=6), 95% of medulloblastomas (n=122), 86% of other embryonal tumors (n=21), 50% of choroid plexus carcinomas (n=4), 42% of high grade gliomas (HGG) (n=117), and 37% of diffuse midline gliomas (DMG) (n=65). Within medulloblastoma subtypes, group 4 tumors had the highest expression, and within the HGG tumor cohort H3.3 G34 mutated gliomas had the highest GPC2 expression. High GPC2 protein expression was validated with medulloblastoma and HGG/DMG primary tumors and cell lines using IHC, Western blot, and flow cytometry. We next developed two potent CAR T cell constructs using the D3 specific scFv directed against GPC2 for testing in brain tumor models. GPC2-directed CAR T cells were tested in vitro against medulloblastoma and HGG cells lines, and in vivo using two patient-derived medulloblastoma xenograft models: Rcmb28 (group 3) and 7316-4509 (group 4). GPC2-directed mRNA CAR T cells induced significant GPC2-specific cell death in medulloblastoma and HGG cellular models with concomitant T cell degranulation compared to CD19-directed mRNA CAR T cells. In vivo, GPC2-directed mRNA CAR T cells delivered locoregionally induced significant tumor regression measured by bioluminescence after 4–6 intratumoral infusions of 4 x 10 6 CAR T cells (p<0.0001 for Rcmb28, p<0.05 for 7316-4509). No GPC2-directed CAR T cell related toxicity was observed. GPC2 is a highly differentially expressed cell surface protein on multiple malignant pediatric brain tumors that can be targeted safely with local delivery of mRNA CAR T cells.